Pelatihan Membaca Al-Qur`an dengan Metode Talaqqi untuk Meningkatkan Kualitas Bacaan bagi Anak-Anak TPA Masjid At Taqwa Kampung Gunung Putri Desa Sukatani - Ahyarudin, Ahyarudin; A. Sifaun Najah; Azzam, Abdullah; Siregar, Fahrul Rozi; Fathulloh, Muhammad Hamzah (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2024)
This service journal aims to find out how much influence the talaqqi method has in improving the quality of a child's reading when reading the Qur'an. This community service activity was carried out on 1-25 Ramadan 1445 Hijriyah, which was attended by 15 participants from the At Taqwa Mosque TPA children, Sukatani Gunung Putri village. This training was carried out based on the needs of partners related to the evaluation of the TPA program itself, namely the lack of attention of children to the quality of reading the Qur'an which had been memorized from short surahs or which had not been memorized from other surahs in the Qur'an. To get results optimally, this training is carried out using a participatory method with a service learning model. This training activity ran well and smoothly in accordance with the stages arranged in the activity implementation schedule that is already in the TPA plus the planning in the teaching process. This can be seen from the achievement of training objectives and the enthusiasm and activeness of participants in training activities.